Association of genetic variants in Wnt signaling pathway with tuberculosis in Chinese Han population. - Xuejiao Hu; Mengqiao Shang; Juan Zhou; Yuanxin Ye; Xiaojun Lu; Chuanmin Tao; Binwu Ying; Lanlan Wang (PLoS ONE, 2014)
Compelling studies have implicated that the Wnt signaling pathway plays an important role in the development and progression of tuberculosis, however, there is little literature addressing the role of polymorphisms in Wnt pathway on tuberculosis. We took a pathway based candidate gene approach to investigate the possible correlation between genetic variants in Wnt pathway and tuberculosis. Three single nucleotide polymorphisms (SNPs) in Wnt pathway (rs4135385 in CTNNB1 gene, rs7832767 in SFRP1 gene, and rs11079571 in AXIN2 gene) were genotyped in 422 Chinese Han tuberculosis patients and 402 frequency matched (age, gender, and ethnicity) controls using high-resolution melting analysis. The genotype and allelic frequencies of rs4135385 and rs7832767 were significantly different among patients and controls. The dominant model of rs4135385 was significantly associated with an increased risk of tuberculosis (AG/GG versus AA: OR = 1.49, 95% CI = 1.06-2.09, p = 0.019). The recessive model of rs7832767 posed a significant higher risk for tuberculosis (TT versus TC/CC, OR = 2.70, 95% CI = 1.41-5.18, p = 0.002). These SNPs were further evaluated whether they were correlated with the site of tuberculosis and the level of inflammatory markers. Rs7832767 was significantly associated with the level of CRP (p = 0.014), and the patients carrying T allele might present with elevated CRP values (OR = 1.90, 95% CI = 1.21-2.96, p = 0.005). Our study provided the first evidence that rs4135385 and rs7832767 were associated with tuberculosis risk, and genetic variants in Wnt signaling pathway might participate in genetic susceptibility to tuberculosis in Chinese Han population. Further epidemiological and functional studies in larger populations are warranted to verify our results.